AB0563 Relationship between Readmission and Corticosteroid Doses in Patients with Antineutrophil Cytoplasmic Antibody-Associated Vasculitis. (10th June 2014) - Isohisa, A.; Tsugihashi, Y.; Sasai, T.; Azuma, T.; Sada, R.; Yamamoto, Y.; Yamaguchi, T.; Fukuhara, S.
Abstract : Background: Although corticosteroid treatment is essential in the management of rheumatic diseases, adverse events of corticosteroids pose serious problems. Antineutrophil cytoplasmic antibody-associated vasculitis (AAV) frequently requires higher corticosteroids doses than does rheumatoid arthritis, and such high doses may cause severe adverse events such as infectious diseases. Few studies have investigated the relationship between the steroid dose and adverse effects in AAV. Objectives: This study aimed to analyze the relationship between readmission of patients with AAV and their corticosteroid dose and to estimate the dose that poses a risk of readmission. Methods: Study Design: A retrospective cohort study with 2-year follow-up after the initiation of corticosteroid therapy. Setting: Tenri hospital, Tenri, Japan. Participants: Patients with AAV who were discharged after the initial corticosteroid therapy from 1990 to 2012. Outcomes: (1) Readmission because of an infectious disease after the initial corticosteroid therapy. 2) Cumulative corticosteroid doses that may cause the readmission because of an infection. Analysis: We performed survival analysis using Kaplan–Meier estimates and the multivariate Cox regression model to calculate the readmission rate related to infectious diseases. In order to define corticosteroid categories (high-dose/low-dose), we drew a boundary using an accumulation model with median corticosteroid doses on each day until readmission or the end of follow-up. We described the cumulative corticosteroid doses in the readmission group with infectious disease. Results: We enrolled 78 participants [mean age (SD): 68.2 (11.8) years]. During the 2-year follow-up, 41 (52%) participants were readmitted because of infectious disease (n=16), relapse (n=10), fracture (n=5), or other reasons (n=10). Of the 16 patients with infections, 9 had bacterial infections (mainly respiratory tract infections), 5 had viral infections, and 2 had fungal infections. The adjusted hazard ratio for readmission due to infectious disease was 1.91 [95% CI: 0.63–5.62] for the high-dose group. The cumulative median steroid dose for readmission because of infection was 4, 896 mg (range: 1, 370–14, 285 mg) as a prednisone equivalent. The median interval from corticosteroid initiation to readmission was 189 days (range: 57–729 days). Conclusions: Among patients with AAV, the high-dose corticosteroid group is more likely to be readmitted than the low-dose group. Readmission due to infectious disease was limited to participants whose cumulative steroid dose was >1370 mg (approximately 2 months after the initiation). Thus, such patients should be carefully monitored for signs and symptoms of infection. References: Hoes JN, Jacobs JWG, Boers M, Boumpas D, Buttegereit F, Caeyers N, Choy EH, Cutolo M, Da Silva JAP, Esselens G, Guillevin L, Hafstrom I, Kirwan JR, Rovensky J, Russell A, Saag KG, Svensson B, Westhovens R, Zeidler H, Bijlsma JWJ. EULAR evidence-based recommendation on the management of systemic glucocorticoid therapy in rheumatic disease. Ann Rheum Dis. 2007; 66: 1560-7. Acknowledgements: This study was supported by a grant-in-aid by Ministry of Health, Labor and Welfare in Japan, "Development of Clinical Research Fellowship" (Grant no: H21-007) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1586